Voice Recognition and Sensor Enable Solar Panel Exhaust Fan Device Using Arduino Uno: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Many people experience overheating and poor ventilation due to years of research byscientists and technologists. It's one of the reasons we don't have a better environment. Theresearchers came up with an idea to make a device that solved this problem. Using solarpanels, this device reduces heat and saves energy. The device is also operated by a sensorthat allows an exhaust fan to work automatically by maintaining room temperature.The results of the research study present the prototype design, control system, and circuitconnection. Arduino IDE has been used to program the Arduino Uno, MAX6675thermocouple, and MQ135 sensor. It is also programmed in Arduino IDE with downloadedlibraries. Depending on the sensors determine the exhaust fan speed. If the sensor reaches34°C-40°C, the exhaust fan will operate at Normal, Moderate, and Maximum. When theMq135 sensor detects toxic gas, the exhaust fan will run at Maximum speed. The result showsvoice recognition has no delay in manually operating the device using voice. The result showsthat a solar panel can produce 18-20 watts per hour, depending on the weather. Therespondents' perceptions of the prototype reliability were gathered through a questionnaire.The demographic profile of the respondents, where age, sex, and educational attainment aredetermined and presented using a pie graph.The voice recognition and sensor solar panel exhaust fan is sensor-based and uses voicerecognition to operate the device manually, and the MAX6675 K- -type thermocouple, MQ135Gas, operates automatically. The components used were compatible with the Arduino Uno. Itsuccessfully runs the prototype operations, the sensors' detection, and the speech manually.A majority of respondents are males aged 29-40. Graduates make up 47% of respondents oneducational attainment. The evaluation shows that the target client agrees with the proposedprototype since the weighted mean of all indicators indicates more than 3, according to theLikert scale rating. The researchers conclude that a microcontroller Arduino Uno is aneffective device for developing a Voice recognition and sensor solar panel exhaust fan device.
Keywords: Computer Science & Engineering